The Survival Benefits of Surgical Resection and Adjuvant Therapy for Patients With Brainstem Glioma - Liu, Zhuoyi; Feng, Songshan; Li, Jing; Cao, Hui; Huang, Jun; Fan, Fan; Cheng, Li; Liu, Zhixiong; Cheng, Quan (Frontiers in Oncology, 2021)
Purpose The role of surgical resection in the treatment of brainstem glioma (BSG) is poorly understood. For pediatric low-grade (LGBSG) group, several monocentric small-scale retrospective studies reported contradictory conclusions. And there was no clinical study focused on surgical resection for adult or pediatric high-grade (HG) patient groups. This study aims to illustrate whether surgical resection and adjuvant therapy provide survival benefits for patients with histologically confirmed BSG. Patients and Methods This retrospective cohort study included 529 patients with histologically confirmed BSG in Surveillance Epidemiology and End Results (SEER) database from 2006-2015. Patients were divided into four groups by age and World Health Organization (WHO) grade. Kaplan-Meier curves of CSS were plotted by different treatment options to compare the survival probability. Univariate and multivariable analyses were then conducted to determine the prognosis effects of surgical resection and adjuvant therapy on cancer specific survival (CSS). All analyses were done in four different groups separately. Results The final sample included 529 patients. The entire study population was divided into groups of pediatric LG (n=236, 44.6%), pediatric HG (n=37, 7.0%), adult LG (n=204, 38.6%) and adult HG (n=52, 9.8%). 52.7% (n=144) of pediatric patients had pilocytic astrocytoma and 45.3% (n=116) of adult patients had ependymoma. Pediatric LGBSG group had the highest gross total resection (GTR) rate (61.4%) and 5-year CSS rate (88.6%). Kaplan-Meier curves of pediatric LGBSG group revealed that patients treated with GTR had significantly better survival probability (P=0.033). Multivariable analysis identified GTR as independently significant predictor for prolonged CSS in pediatric LGBSG group (HR0.29, 95%CI 0.11-0.78, P=0.015); Surgical resection showed no relation to CSS in other patient groups. Kaplan-Meier curves of adult HGBSG group showed that patients treated with both RT and CT in adult HGBSG group had the best survival probability (P=0.02). However, multivariable analysis showed the combination of radiotherapy (RT) and chemotherapy (CT) was not significantly related to better CSS in adult HGBSG group (HR0.35, 95%CI 0.11-1.09, P=0.070). Adjuvant therapy didn’t associate with better CSS in other patient groups. Conclusion Pediatric LGBSG group had the highest GTR rate and the most favorable clinical outcome. GTR can provide significant survival benefits for pediatric LGBSG group.